THE CORRELATION BETWEEN PERCEPTION ON TEACHERâ€™S CREATIVITY AND ENVIRONMENT TOWARD ENGLISH ACHIEVEMENT AT THE SECOND YEAR STUDENTS OF MAN KRECEK PARE KEDIRI - Wibowo, Yuswi Adi (LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
This research is aimed to find out the influence of perception on teachersâ€™ creativity (X 1 ) and environment (X 2 ) toward English achievement (Y) among the second year students in MAN Krecek Pare Kediri in academic year 2015. The quantitative approach was used to design this research. The techniques were partial correlation and simultaneous regression. The instruments were questionnaires and test. The subject of this research was the second year students while the sample of this research was 175 students. From the result of simultaneous and partial correlation, it is found that the value of â€œrâ€ coefficient was 0,866 while the â€œrâ€ table at the level of significance 1%  is 0.181 and 0.138 at 5% (0.181<0.866>0.138). It means that there is positive and significance correlation between the perception on teacherâ€™s creativity and learning environment toward English achievement of students of MAN Krecek Kediri. The result is strengtened by the result of SPSS that is significant at two tailed. It is also strengthened by the number of significance (2-tailed) 0.001. So, the alternative hypothesis was accepted. Based on this accepted hypothesis, it is found that 86.6% of the perception on teacherâ€™s creativity influence the English achievement and 13.4% of the perception on teacherâ€™s creativity does not influence the English achievement. And, it is found that 86.6% of the learning environment influences the English achievement and 13.4% of the learning environment does not influence the English achievement. After seing the result, to increase the studentsâ€™ English achievement, it is recommended for further researcher to be a source to conduct the next research. The content is recommended to be perfected by the next researcher.